Preferred thinking styles of gifted students and the implications for curriculum development - ELLALA, Z.K.; ABU-ATTIYEH, J; ALGHAZO, E.M (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT A sample of 250 students (121) males and (129) females in grades 10-12 participated in this study of their preferred thinking methods. The Methods of Thinking Assessment, which was prepared by Sternberg and Wagner (1991), was used as the data gathering tool. Analysis of data revealed that the preferred methods of thinking were in descending order; legislative, external, hierarchical, judicial, conservative, anarchist, local, internal, monarchic, and global. Also, analysis of data revealed significant differences in all dimensions of the overall score being better for female students; however, no significant differences were found about grade level. Una muestra de 250 estudiantes (121) hombres y (129) mujeres en los grados 10-12 participaron en este estudio de sus métodos de pensamiento preferidos. Los métodos de evaluación del pensamiento que fueron preparados por Sternberg y Wagner (1991) se utilizaron como herramienta de recopilación de datos. El análisis de los datos reveló que los métodos de pensamiento preferidos estaban en orden descendente; legislativo, externo, jerárquico, judicial, conservador, anarquista, local, interno, monárquico y global. Además, el análisis de los datos reveló diferencias significativas en todas las dimensiones de la puntuación general que es mejor para las alumnas.